2021
DOI: 10.3390/cells10051149
|View full text |Cite
|
Sign up to set email alerts
|

Highly Correlated Recurrence Prognosis in Patients with Metastatic Colorectal Cancer by Synergistic Consideration of Circulating Tumor Cells/Microemboli and Tumor Markers CEA/CA19-9

Abstract: Circulation tumor cells (CTCs) play an important role in metastasis and highly correlate with cancer progression; thus, CTCs could be considered as a powerful diagnosis tool. Our previous studies showed that the number of CTCs could be utilized for recurrence prediction in colorectal cancer (CRC); however, the odds ratio was still lower than five. To improve prognosis in CRC patients, we analyzed CTC clusters/microemboli, CTC numbers, and carcinoembryonic antigen (CEA)/carbohydrate antigen 19-9 (CA19-9) levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…CEA/CA 19-9 are serum tumor biomarkers in CRC that are extensively deployed within clinic-based settings. CEA/ CA 19-9 are non-invasive and easily available cancer biomarkers concerning CRC immediate monitoring/prediction during early, advanced, and metastatic CRC [10][11][12]. Notwithstanding, to the best of our knowledge, clinical values within the normal range have not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…CEA/CA 19-9 are serum tumor biomarkers in CRC that are extensively deployed within clinic-based settings. CEA/ CA 19-9 are non-invasive and easily available cancer biomarkers concerning CRC immediate monitoring/prediction during early, advanced, and metastatic CRC [10][11][12]. Notwithstanding, to the best of our knowledge, clinical values within the normal range have not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical utility of identifying circulating tumour cells in colorectal cancer patients has already been described by several authors [ 15 , 22 , 23 , 25 , 27 , 38 , 39 ]. However, current protocols for the isolation and characterisation of CTCs are mainly limited to the microscopic evaluation of one or two markers, compromising the ability to identify different CTC subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies on CTCs have relied solely on the expression of epithelial markers (EpCAM/CK) versus the absence of CD45 expression [ 12 , 24 ], reducing the ability to detect/characterise CTCs and thus weakening their prognostic value [ 26 ]. Furthermore, poor prognosis is associated not only with CTC counts but also with CTC clusters (also called microemboli), as they increase with disease stage and are significantly associated with worse outcomes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…And secondly, they are larger than single CTCs, and more likely to be trapped in blood vessels, leading to greater colonization efficiency. Previous studies have reported the presence of homotypic CTC clusters causes significantly worse progression or poor prognosis in breast, [43,52,56] colorectal, [57,58] gastric cancer, [59,60] pancreatic ductal adenocarcinoma, [61] and small-cell lung cancers. [31] Heterotypic CTC clusters consists of aggregates of cancer cells with non-malignant stromal or immune cells.…”
Section: Ctcs Exist In Circulation Either As Individual Cells or As C...mentioning
confidence: 99%